0220 Changes in Light Exposure During the Daylight Saving Time to Standard Time Transition. (25th May 2022) - Linton, Sabrina; Withrow, Dana; Wright, Kenneth; Rodheim, Katrina
Abstract: Introduction: Although sunrise and sunset do not change, the Daylight Saving Time (DST) to Standard Time (ST) transition results in an earlier clock hour of sunrise and sunset. It has been hypothesized that ST results in brighter mornings and dimmer afternoons/early evenings compared to DST. However, how the time change from DST to ST influences light exposure measured at the level of the individual has not been quantified. Thus, we aimed to determine if the time change from DST to ST increases morning and decreases evening light exposure under typical living conditions. Methods: 25 young healthy adults [7 males (25.6±7.8yr; mean±SD)] completed a 2 week-long at home protocol. Light exposure was collected with wrist worn Actiwatch Spectrum Plus (Philips Respironics, Bend, OR) one week prior and one week after the transition from DST to ST in Fall 2020. Participants were instructed to continue with their typical work/school schedule, to maintain a nighttime sleep schedule, and to not stay up all night throughout the study. Data were analyzed comparing light exposure levels in the morning (0600-1200h) and afternoon/early evening hours (1200-1800h) across the work/school week with mixed model ANOVA and planned comparisons assessed. Results: A significant week by time-of-day by week interaction (p<0.05) was observed showing brighter light exposure levels in the morning during the week after the change from DST to ST (p < 0.01), whereas similar light exposure levels were observed in the afternoon/evening hours across weeks (p = 0.64). Conclusion: Consistent with expectations, individuals were exposed to brighter mornings but contrary to expectations individuals were not exposed to dimmer afternoons/early evenings during ST versus DST. Early morning light exposure is important for entrainment of the on average longer-than-24-hour human circadian period to the 24h day, and for maintenance of sleep schedules that are conducive to work/school start times. Future research is needed to highlight the health, performance, and safety benefits of brighter morning light exposure demonstrated here during ST, especially given current efforts to end the time change between DST and ST. Support (If Any):